Handbook of Developmental Science, Behavior, and Genetics 2010
DOI: 10.1002/9781444327632.ch6
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Environment, Experience, and Learning in Behavioral Development

Abstract: In the science of behavioral development, we want to understand how the complete behavioral repertoire of an individual develops along trajectories (starting from conception and proceeding through differences in forms and processes across the lifespan) that yield both individual differences and species-typical similarities. For some decades, the conceptual frame for examining such questions was that behavior developed from an organism-environment interaction. The task for the developmental scientist was to dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
3
2
1

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 106 publications
(109 reference statements)
0
23
0
Order By: Relevance
“…Michel, 2010b). As Sperry (1965) predicted, molecular biology revealed that the DNA (the instantiation of the gene construct) is part of a complex system (network) of causes that operates throughout the life span.…”
Section: Gene-by-environment Interaction (Transactional Models)mentioning
confidence: 99%
See 3 more Smart Citations
“…Michel, 2010b). As Sperry (1965) predicted, molecular biology revealed that the DNA (the instantiation of the gene construct) is part of a complex system (network) of causes that operates throughout the life span.…”
Section: Gene-by-environment Interaction (Transactional Models)mentioning
confidence: 99%
“…The notion of genetic predisposition is an Downloaded by [North Dakota State University] at 07:26 12 October 2014 inappropriate attribution of developmental control to genes and an empirically unsubstantiated explanation of which factors affect developmental trajectories. The DNA is only a contributing factor in the functioning of the individual's physiological systems and experience can only influence those systems to the degree that they are transduced by sensory systems into physiological processes (Michel, 2010b).…”
Section: What Is Developmental Psychobiology?mentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, DPB research is well positioned to provide insights into these extragenetic influences on behavioral development, because we have a long history of doing exactly that. Indeed, DPB found that "genes" are only one mechanism for carrying "information" from parental to offspring populations to produce the transgenerational concordance of phenotypes ( Michel, 2010a;Michel & Moore, 1995). In addition, although genes may be involved differently at various points in any developmental trajectory for a psychological characteristic, they are neither governing nor primarily responsible for that trajectory.…”
Section: A Dpb Approach Can Help Connect Psychology With Biologymentioning
confidence: 99%